Digitization of Malay Culture Through the Malay House Program for Teenagers in Madrasah Aliyah Al Fajri Tanjungbalai - Karina, Nina; Perangin-angin, Alemina Br.; Prasetya, Fikry (Universitas Negeri Medan, 2023)
Abstract “ The writing of this journal aims to (1) become a forum for people who are interested in learning About Malay culture, (2) provide facilities in helping to improve the soft skills of adolescents while still implementing local wisdom, (3) reintroduce local cultural wisdom to students, such as the culture of guiding, bersajak, and storytelling typical of Malay; and (4) improving the quality of students to become an outstanding and cultured student. The research partner is Madrasah Aliyah Al Fajri Tanjung Balai, with a total participation of 22 students from class X to class XII. Digital-based Rumah Melayu activities through digital content creation training are carried out through a panel of lectures and discussions with participatory methods, so the training participants participate in every stage of the activities. The results showed that (1) it can be seen that the percentage of students who have an interest in Malay dance art is 85%, while for the art of guiding and storytelling, each is 31%, and 31% (2) as many as 90.3% of students claim to be helped by the cultural digitization project made (3) there are 4.5% of students who do not respond to the first and third questions. (4) while for the second question, 9.1% of children did not respond. Based on the research findings, it can be concluded that (1) the digitization of Malay culture provides a forum to channel students' interests in the classroom and also provides an opportunity to express themselves, (2) the student's Malay culture digitization program can better preserve and introduce local culture to the broader community through the internet (3) through the Malay culture digitization project, students can further develop their creativity and ability to use technology (4) finally, the students also agreed that through the project of digitizing Malay culture they could increase their confidence in working through the internet.Keywords: Digitalization, Melayu, Program, Students